Pathogen dynamism and variability of rice yellow mottle virus in Kenya - Kigaru, Antony; Nganga, Everlyne M.; Murori, Rosemary; Pappu, Hanu R.; Runo, Steven; Ateka, Elijah M. (Springer, 2025)
Rice yellow mottle disease (RYMD) continues to constrain rice production in Africa. Rice yellow mottle virus (RYMV), which belongs to the Sobemovirus genus, is the causal agent of RYMD. In Kenya, previous studies on RYMV mostly focused on western Kenya, ignoring the central and coastal regions, which are also important areas for rice cultivation in the country. This has resulted in incomplete data on RYMD outbreaks. This study aimed to determine the prevalence of RYMD in the farmers' fields, and the genetic diversity of the RYMV based on the coat protein gene. Field surveys were carried out in Kenya's rice-growing regions between May and July 2023 to determine disease incidences using the IRRI Standard Evaluation Scale (SES) for rice. Symptom observations and serological tests confirmed the presence of RYMV in all surveyed rice cultivation areas. The presence of RYMV was detected in Kirinyaga, Tana River, and Taita Taveta counties of Kenya, representing the field report of its occurrence in these regions. Disease incidence and severity analysis using one-way ANOVA showed no significant difference in RYMD incidence among the rice irrigation schemes (F (6,29) = 1.838, P = 0.1265). Sequencing results of the coat protein gene (ORF4 region) revealed that the RYMV isolates in this study could be classified as S4ke, S4ug, and S4mg strains in the East Africa lineage. The discovery of the RYMV strain S4mg in Kenya runs counter to the gradual strain of breaking up and moving away that has been established in Africa over the past two centuries. Results showed that RYMV is present in all the rice-growing regions under study and exhibits intra-strain diversity in Kenya. Incorporating resistance genes into extensively grown rice cultivars is crucial for preventing the spread of the rice yellow mottle virus.